The national cultural dimensions influence on celebrity endorsement - Markovic, Ivana; Rabasović, Biljana; Borisavljević, Katarina (Serbian Journal of Management, 2026)
Celebrity endorsement is one of the most effective promotional strategies and, as such, is widely present in both domestic and international marketing. The application of this promotional strategy in global marketing requires adaptation depending on the cultural patterns of consumer behavior in the international environment. Accordingly, the subject of this study is the influence of culture on the effect of celebrity endorsement within the global context. The study aims to examine the impact of national cultural dimensions, based on Hofstede’s model (power distance and individualism/collectivism) on the perceptions of respondents from different cultural backgrounds regarding the appearance of celebrities in promotional activities, the perceived quality of products endorsed by celebrities, the attractiveness and credibility of celebrities. Primary data was collected using the method of personal interview, applying an online survey technique. A total of 353 respondents from 70 different nationalities participated in the study. The research hypotheses were tested using group comparison techniques, specifically the independent samples t-test. The results suggest that celebrity endorsement is more favorable in collectivistic and high power distance cultures in comparison to individualistic and low power distance cultures. The theoretical contribution of the study lies in providing new insights into the influence of culture on consumer behavior. The findings may serve as guidelines for marketing managers in developing a marketing strategy plan for international markets, which can be considered a practical contribution of the study